The Role of Engineering Ethics on Concrete Fire Safety - Yahaghi, Javad; Sorooshian, Shahryar (Springer Netherlands, 2018)
As concrete has high specific heat and low thermal conductivity, it has a high capacity to bear high temperatures and fire (Tanyildizi and Coskun 2008). Nevertheless, high temperatures are found to have an impact on its features like surface appearance, elasticity, colour, compressive strength and concrete density. When a new construction material is used, it is important to study and understand all the behavioural aspects of that material because human safety in case of any mishaps such as a fire outbreak is one of the key factors to be considered in the design of buildings.